Revitalisasi Taman Balai Desa Bicak, Kecamatan Trowulan, Kabupaten Mojokerto - Alayda Rahma Putri Aditya; Ilham Janatuka Al Firdaus; Sjarief Hidajat (CV. ALIM'SPUBLISHING, 2024)
. KKN is one of the community service activities carried out by students from universities. KKN-T Bela Negara of National Development University “Veteran” East Java was conducted in Bicak Village, Trowulan, Mojokerto. The work program carried out by the KKN-T Bela Negara Group 04 Wave 2 was the revitalization of the Bicak Village Hall park. The park is an open area that has several types of plants, trees, shrubs, bushes and grasses. The condition of the garden at Bicak Village Hall is poorly maintained, some plants are dead and overgrown with grass. This revitalization activity is carried out with several methods from direct observation and survey. As for some of the activities carried out in revitalizing the park, such as community service cleaning the park area and Bicak Village Hall, arranging rocks in the area to the right and left of the park, and planting several ornamental plants. Group 04 Wave 2 KKN-T Bela Negara revitalized the Bicak Village Hall park which aims to increase the SDGs score of the Environmentally Concerned Village, improve the function of the park and increase the aesthetic value of the Village Hall.